2018
DOI: 10.26434/chemrxiv.6148940
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Chemoproteomics to Understand the Role of Selected Psychoactives in Treating Mental Health Indications

Abstract: <div> <div> <div> <p>We have developed the Computational Analysis of Novel Drug Opportunities (CANDO) platform to infer homology of drug behavior at a proteomic level by constructing and analyzing structural compound-proteome interaction signatures of 3,733 compounds with 48,278 proteins in a shotgun manner. We applied the CANDO platform to predict putative therapeutic properties of 428 psychoactive compounds that belong to phenylethylamine, tryptamine, and cannabinoid chemi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…We have used our AIA metric in CANDO extensively [7][8][9][10][11][12][13][14][15][16][17] (section "Drug/compound characterization, benchmarking, evaluation metrics, and performance"). Similarly, Peyvandipour et al used a custom evaluation metric in their systematic drug repurposing study [83].…”
Section: Custom Methods Of Performance Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…We have used our AIA metric in CANDO extensively [7][8][9][10][11][12][13][14][15][16][17] (section "Drug/compound characterization, benchmarking, evaluation metrics, and performance"). Similarly, Peyvandipour et al used a custom evaluation metric in their systematic drug repurposing study [83].…”
Section: Custom Methods Of Performance Evaluationmentioning
confidence: 99%
“…We developed and deployed the CANDO platform to model the relationships between every disease/indication and every human use drug/compound [7][8][9][10][11][12][13][14][15][16][17]. Built upon the premise of polypharmacology and multitargeting, at the core of CANDO is the ability to infer similarity of compound/drug behavior.…”
Section: Computational Analysis Of Novel Drug Opportunities (Cando)mentioning
confidence: 99%
See 2 more Smart Citations
“…29 Recently, it has been shown that molecular sub-graph features incorporated through a GNN and protein features encoded by their sequence can be combined to predict if a compound can target a given protein. 24 Inspired by this work and based on our interest in developing methods for drug design and immunology [29][30][31][32][33][34][35][36] , we have developed a new machine learning model to predict if a compound can inhibit the PD-1/PD-L1 interaction. Our method replaces the protein sequence features with docking scores representing the free energy of binding and due to this global energetic interaction of the small molecule in the binding pocket, we have termed this model as an "Energy Graph Neural Network" (EGNN).…”
Section: Introductionmentioning
confidence: 99%